Value of Visceral Fat Area and Resting Energy Expenditure in Assessment of Metabolic Characteristics in Obese and Lean Nonalcoholic Fatty Liver Disease - Ye, Qing; Yan, Junqing; Xiao, Hui-Juan; Han, Tao (Turkish Journal of Gastroenterology, 2021)
Background: The high prevalence and incidence of non-alcoholic fatty liver disease (NAFLD) have become a global medical concern. Compared with obesity, metabolic abnormalities may be more critical. Currently, there is lack of relevant data for nutritional status and energy metabolic characteristics in patients with obese and lean NAFLD. Methods: All the enrolled NAFLD patients were divided into 2 groups: the obese group (205 patients with body mass index (BMI) ≥ 25 kg/m2) and the lean group (73 patients with BMI < 25 kg/m2). Using a body composition analyzer, we analyzed their nutritional status including skeletal muscle, body fat, protein content, and visceral fat area (VFA). Energy metabolic characteristics including resting energy expenditure (REE), respiratory quotient, and oxidation rate of 3 major nutrients (carbohydrate, CHO%, fat, FAT%, and protein, PRO%) were analyzed by metabolic cart. Results: The lean NAFLD patients’ LDL-c and UA even increased significantly than the obese patients (P = .001 and .006, respectively). Compared with the control group, VFA and REE were significantly higher in the lean NAFLD group (P = .008, P < .001 respectively). CHO%, FAT%, and PRO% in the lean NAFLD group were 29.31 ± 7.07%, 55.59 ± 12.09%, and 15.10 ± 4.07%, respectively, and there was no significant difference compared to the control. However, compared to the obese NAFLD group, their CHO% increased, whereas FAT% decreased (both P < .001). Conclusion: NAFLD patients suffer from nutritional imbalances and energy metabolic abnormalities, regardless of whether they are associated with obesity. LDL, UA, VFA, and REE can be used as good evaluation indicators.